2006
DOI: 10.1534/genetics.105.052829
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Targeting in Drosophila With Zinc-Finger Nucleases

Abstract: This report describes high-frequency germline gene targeting at two genomic loci in Drosophila melanogaster, y and ry. In the best case, nearly all induced parents produced mutant progeny; 25% of their offspring were new mutants and most of these were targeted gene replacements resulting from homologous recombination (HR) with a marked donor DNA. The procedure that generates these high frequencies relies on cleavage of the target by designed zinc-finger nucleases (ZFNs) and production of a linear donor in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
222
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(229 citation statements)
references
References 62 publications
6
222
1
Order By: Relevance
“…In many cases, ZFN-mediated DSBs have been used to stimulate the HR DNA-repair machinery for HR-mediated gene replacement and gene addition. This approach has been successfully implemented in animals (Beumer et al, 2006;Meng et al, 2008), human cell lines (Urnov et al, 2005;Lombardo et al, 2007), and plants (Wright et al, 2005;Cai et al, 2009;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013). However, it is important to note that while ZFNinduced DSBs can indeed induce the HR repair machinery, most of these breaks are repaired by the cell's NHEJ DNA-repair machinery in plant and other species.…”
mentioning
confidence: 99%
“…In many cases, ZFN-mediated DSBs have been used to stimulate the HR DNA-repair machinery for HR-mediated gene replacement and gene addition. This approach has been successfully implemented in animals (Beumer et al, 2006;Meng et al, 2008), human cell lines (Urnov et al, 2005;Lombardo et al, 2007), and plants (Wright et al, 2005;Cai et al, 2009;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013). However, it is important to note that while ZFNinduced DSBs can indeed induce the HR repair machinery, most of these breaks are repaired by the cell's NHEJ DNA-repair machinery in plant and other species.…”
mentioning
confidence: 99%
“…These custom zinc finger proteins can be attached to other protein domains to direct various functions to specific locations in the genomes of cells and organisms (10). When fused to the nonspecific DNA cleavage domain of the FokI restriction endonuclease, zinc fingers can direct double-strand breaks (DSBs) to disrupt specific genes (11)(12)(13)(14) or in combination with a repair template to induce gene correction via homologous recombination (HR) (15)(16)(17)(18). Thus, ZFNs show promise for the treatment of monogenic disorders by promoting the knockout or correction of specific genes.…”
mentioning
confidence: 99%
“…Meganucleases such as I-SceI are valuable cleavage reagents because of their long recognition sites (19-21), but their sites must be introduced before they can be attacked. Because zinc fingers exist for many of the DNA triplets, nucleases of this type can theoretically be created to target almost any preexisting locus.Studies performed in Drosophila and in human cells have shown that ZFNs can be designed to effectively cleave specific sequences (22)(23)(24)(25)(26)(27)(28). Additional studies with synthetic targets have demonstrated the efficiency of ZFN-directed cleavage in Xenopus, in mammalian cells and in plants (16,(29)(30)(31).…”
mentioning
confidence: 99%